Night road - Jenkins, A. M. (Amanda McRaney) (New York : HarperTeen, 2008)
Cole, a hemovore who feeds off of human blood, is asked to take another heme out for training, but, Gordon, his new charge, is having difficulty leaving his old life behind and his actions soon threaten them both.
Horn Book.
Kliatt.
Young Adult
Keywords: Automobile travel -- Juvenile fiction; Conduct of life -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Vampires -- Juvenile fiction; Automobile travel -- Fiction; Conduct of life -- Fiction; Self-actualization (Psychology) -- Fiction; Vampires -- Fiction; Automobile travel -- Fiction; Conduct of life -- Fiction; Horror fiction; Self-realization -- Fiction; Vampires -- Fiction; Horror fiction